Toleransi Dalam Pendidikan Agama Dan Implementasinya Terhadap Perilaku Toleran Peserta Didik di SMA Negeri 1 Gerung Lombok Barat - Nur Hayati (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2019)
This research aim to unveil (1) how the tolerant traits were implement toward other religious believers and its implementation in everyday life (2) and factors promoting the implication of the tolerant life. This descriptive qualitative research with phenomenological approach collected the data trough observations, interviews, and documentation, in which the data were triangulated using the descriptive socio-historical analysis method. The findings showed that (1) the students of SMA Negeri 1 Gerung knew the concepts of tolerance from their parents and elementary schooling, (2) that the appropriate implementation of tolerant traits for the students included the respecting ach other and respecting other religious believers, (3) and that factors promoting the tolerance were the school headmasters, religious understanding, and school culture. The implication of that was that learned could live in harmony, could run their own religious life according to their beliefs, and they did not find obstacles in tolerating.